Sexual dimorphism, pattern of third molar and mandibular second premolar agenesis in Indian paediatric orthodontic patients - Apurva Mishra; Ramesh K. Pandey (Elsevier, 2017)
Objective: To determine and compare the prevalence and pattern of agenesis of third molar and mandibular second premolar in paediatric orthodontic patients of age group 9-15 for sexual dimorphism. Methods: The digital orthopantograph was obtained from the archive record of patients of age group 9-15 year. Radiographs of 301 patients were evaluated after taking exclusion criteria into account and were assessed for the presence/absence of third molars and mandibular second premolar. Tooth development evaluation followed the method of Demirjian et al., based on eight stages of tooth formation. The agenesis of third molar in maxilla and mandible between age groups and gender was compared using Chi-squared test. Results: The rate of agenesis of third molars was observed 36.8% in the present study. Twenty-four (24.3%) percentage of the study population showed agenesis of all the four third molars. The agenesis of third molars was found to be higher among males than females (p > 0.05). Prevalence of agenesis of mandibular second premolar was 4.7-5%. Conclusions: Agenesis of third molars was more commonly seen in the maxilla, having male predilection. Maxillary right third molar was the most commonly missing tooth irrespective of gender. Keywords: Tooth agenesis, Third molar, Mandibular second premolar, Paediatric orthodontic patients, Pattern of agenesis, Missing third molar